Trading Human Rights for Cheap Products: The Rise of China and the End of the Liberal World Order in the Context of the Russia-Ukraine War - Hanna Samir Kassab (Contemporary Chinese Political Economy and Strategic Relations: An International Journal, 2022)
In 1995, Michael J. Sullivan questions whether China’s human rights violations would cease given increased trade with the democratic world. Today, the United States and the European Union import more from China than any other major power or state. The European Union, a defender of international human rights as enshrined in its constitution, is working on a major investment deal with China. However, China’s human rights record did not improve; rather, China continues to violate the rights of Uyghurs, Buddhists, and other ethnic and religious minorities like Falun Gong practitioners and Christians. It now has the potential to directly challenge the liberal order of the United States. The Russian invasion of Ukraine will only increase China’s power and influence. Russian isolation resulted from Western-backed sanctions generates an economic dependency on China. Thus, China’s military power and political influence will continue to increase, furnishing its position as a counter-hegemonic power to the United States. This article’s first task is to deconstruct liberal and neoliberal institutionalism theoretical frameworks that dominated American foreign policy architecture since the early 1980s. Its focus on absolute gains enabled China’s rise regardless of its totalitarian stance, specifically its human rights violations. China’s influence is now global as it exports its development model to developing states. Democratic states are thus responsible for the rise of China.